El sistema de bancos sombra y la inestabilidad financiera internacional - Andrés Blancas Neria; Manuel Gómez Lira (Atlantic Review of Economics, 2017)
– The aim of this paper is to analyze and highlight the structure and functioning of shadow banks as institutions that played a key role in the 2008 financial crisis, which may contribute to identify financial risks in the future. The interrelated growth of shadow banks through their balance sheets is the process that is identified as a mechanism of financial feedback that is transformed into financial fragility and endogenous Minsky-type finance. Shadow banks are the channel of transmission of international financial fragility and not the securitization and the instruments that emerged from this process (CDO, synthetic CDO and CDS) as has been argued. Shadow banks trade and create market for these instruments at the international level, so that the origin and prevention of the international financial crisis can take a broader and better explanation.
Keywords: E12; G23; F34; C4; 330; Shadow banks; International financial fragility; International financial crisis; Securitization; Synthetic instruments; Graphos; Granger causality